Failure evaluation of SA 210C riffle water wall tubes in 70 MW CFBC boiler. (January 2019) - Senthur Prabu, S.; Choudhary, Ayush; Mittal, Nipun; Gupta, Sahil; Ramkumar, Devendranath; Natarajan, Arivazhagan
Abstract: Boiler tubes used as water walls made up of ferritic steels is having some finite life, because of prolonged exposure in the furnace at elevated temperature, stress and aggressive environment, tube failure taking place. Now a day's premature failure of the boiler tube mainly in water walls is one of the very common phenomena in the thermal power plants. The present investigation was done on the as-received ASTM SA 210C failed boiler tube steel used as water walls in the Circulating Fluidized Bed Combustion (CFBC) coal fired thermal power plant. An attempt has been made to understand the cause, because identifying correct failure mechanism often helps to perform meaningful life assessment and also to prevent the future Boiler Tube Failure (BTF). The as-received of failed tube along with the parent (unused) tube from the water wall raiser panel were selected to study for mechanical and metallurgical properties. Tensile test and micro hardness examinations were carried out on both the parent tube and failed tube. Visual examination reveals "fish-mouth" appearance of the as-received failed tube because of short-term overheating. The micro structure of the parent metal has the conventional structure of ferrite (white constituent) and pearlite (dark constituent), whereas for the as- received failed tube reveals Widmanstatten ferrite. A detailed structure - property relationship has been made by using the combined techniques of Optical Microscopy (OM), SEM/EDAX and XRD. Tensile fractography depicts the presence of micro-voids coalescence in the fibrous network shows ductile mode failure in the as-received failed boiler tubes. Highlights: Failure analysis was carried out on the SA 210C riffle water wall tubes. The microstructure of ruptured surface exhibits the Widmanstatten ferrite. The tensile study reveals that the mode of failure is ductile. The major amounts of Fe2 O3, Fe3 O4 and SiO2 were observed from XRD.